2010
DOI: 10.5130/ajceb.v10i4.1675
|View full text |Cite
|
Sign up to set email alerts
|

Using Purchasing Power Parity to Assess Construction Productivity

Abstract: For many reasons comparing construction productivity between countries is a difficult task. One key problem is that of converting construction costs to a common currency. This problem can be overcome relatively simply by using a basket of construction materials and labour, termed a BLOC (Basket of Locally Obtained Commodities), as a unit of construction cost. Average BLOC costs in each location are calculated from data obtained from a number of sources (quantity surveyors, estimators). Typical building costs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…When the worst-case scenario occurs, skip the blame game and point at the risk strategies of the developers. Such form of qualified property insurance and all the principals involved shall protect the policy (Dai et al 2009;Best 2010;Panas and Pantouvakis 2015;Sezer 2015).…”
Section: The Blame Gamementioning
confidence: 99%
“…When the worst-case scenario occurs, skip the blame game and point at the risk strategies of the developers. Such form of qualified property insurance and all the principals involved shall protect the policy (Dai et al 2009;Best 2010;Panas and Pantouvakis 2015;Sezer 2015).…”
Section: The Blame Gamementioning
confidence: 99%
“…Yi and Chan (2013) make the point that studies focusing on construction productivity are relatively scarce and lack attention to productivity metrics. Productivity research typically falls into two categories: productivity derived from the price paid for construction (Best, 2010) vs the labour, plant and equipment resources employed to construct a building (Thomas and Zavrski, 1999). These approaches are employed at both the macro and micro levels and are case specific (Edkins and Winch, 1999).…”
Section: Principles Surrounding Construction Productivity Measurementmentioning
confidence: 99%
“…Construction industry experienced a downward trend in the productivity growth [9] [13] [10] [11] The study pertaining to causes of time, cost overruns and low productivity in construction projects have been conducted worldwide The productivity of UK's construction sector is declining and it is lower than as compared to few European countries [17] [22] Construction productivity has been affected by a number of factors, which tend to losses of revenues, delay in completion, poor quality and other issues in construction projects [7] The decline in productivity is one of the dangers to the economy, because it creates social conflict, and creates inflationary pressure [19] [25] The authors concluded that the growth in construction productivity is negative [24][6]…”
Section: Impacts Referencesmentioning
confidence: 99%